Integrating artificial intelligence as a catalyst for entrepreneurship education in higher education: a conceptual framework for Indonesian higher education - Heru Wijayanto Aripradono (Privietlab, 2026)
This article proposes a conceptual framework for integrating Entrepreneurship Education, Artificial Intelligence Technology, and Educational Technology as a transformative catalyst for Higher Education in Indonesia. Higher education in Indonesia currently faces difficult challenges, where universities are required to produce graduates who are not only competent but also creative, innovative, and adaptive so that they can overcome the high unemployment rate among young people. A systematic literature review, which refers to entrepreneurship theories and the latest trends in Artificial Intelligence and education technology (over the past five years), reveals the synergistic potential of technology in shaping entrepreneurial mindsets and skills that are relevant to the needs of the times. Although Indonesia's digital ecosystem can be said to have developed rapidly and there are national policies from Indonesia Government related to AI, the implementation process faces significant challenges, such as infrastructure gaps and human resource readiness. The framework proposed in this study describes a holistic approach that includes AI-enriched curricula, Educational Technology-driven pedagogy, a robust digital support ecosystem, and AI-based assessment and analysis, all tailored to the Indonesian context. This article recommends strategic investment in digital infrastructure, capacity building for teaching staff, cross-sector and multi-stakeholder partnerships, and a robust AI ethics framework to realize the vision of higher education that produces socially responsible, ethical, and impactful entrepreneurs.